Development And Characterisation Of Bioactive Glass Based Polymer Composite Film For Potential Application In Wound Healing - Sujon, Mamun Khan (2024)
Tissue engineering is a thriving research area of interest, focuses on the repair, regeneration, and replacement of damaged tissues and organs. This study introduces a novel resorbable advanced wound dressing designed to expedite wound healing and reduce clinical waste, hospitalisation durations, and financial burdens. Bioactive glasses (bgs), traditionally associated with mineralised tissue regeneration, have shown enormous promise in soft tissue repair, particularly in wound healing through the controlled release of therapeutic ions. The incorporation of natural polymer chitosan (cs) and synthetic polymer poly-ε-caprolactone (pcl) into the composite enhances biocompatibility, anti-bacterial activity, surface morphology, and mechanical strength. Different bg compositions (45s5 and 50s8p) were synthesised using sol-gel method and incorporated with cs and pcl to fabricate bg/polymer composite films via a cost-effective solvent-casting technique. A comprehensive analysis was conducted for structural, chemical, morphological, and mechanical characterisation of the composite film. In-vitro bioactivity assays in simulated body fluid assessed the composite film’s potential to induce hydroxycarbonate apatite (ha) formation. Biological impact was evaluated using alamar blue assay and scratch migration assays with human primary dermal fibroblast cells. Anti-bacterial efficacy against staphylococcus aureus (s. Aureus) was examined using agar disc diffusion and minimum inhibitory concentration assays.